Targeting quantum dots to surface proteins in living cells with biotin ligase - Mark Howarth; Keizo Takao; Yasunori Hayashi; Alice Y. Ting (2005)
Escherichia coli biotin ligase site-specifically biotinylates a lysine side chain within a 15-amino acid acceptor peptide (AP) sequence. We show that mammalian cell surface proteins tagged with AP can be biotinylated by biotin ligase added to the medium, while endogenous proteins remain unmodified. The biotin group then serves as a handle for targeting streptavidin-conjugated quantum dots (QDs). This labeling method helps to address the two major deficiencies of antibody-based labeling, which is currently the most common method for targeting QDs to cells: the size of the QD conjugate after antibody attachment and the instability of many antibody-antigen interactions. To demonstrate the versatility of our method, we targeted QDs to cell surface cyan fluorescent protein and epidermal growth factor receptor in HeLa cells and to alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) receptors in neurons. Labeling requires only 2 min, is extremely specific for the AP-tagged protein, and is highly sensitive. We performed time-lapse imaging of single QDs bound to AMPA receptors in neurons, and we compared the trafficking of different AMPA receptor subunits by using two-color pulse-chase labeling.